Asphalt Concrete Quality Assurance During Production - Kazys Petkevičius; Julius Christauskas (The Baltic Journal of Road and Bridge Engineering)
The quality of asphalt concrete mix depends on the quality of mineral materials, on the quality of bitumen and additives, the uniformity of composition of asphalt concrete mix at the plant. The practice revealed that even when modern technologies are used for producing mixtures, the asphalt concrete mix is of insufficiently high quality because effective methods of its quality control are not applied. Recommendations as to the application of the principles of quality control of asphalt concrete mix during production contained in the present work will contribute to improving the quality of asphalt concrete pavement. The present work purpose was to gather information on asphalt concrete components in order to establish realistic asphalt cocrete mix components tolerances during production for ensuring a high quality product.